من مخطوطات أعلام المالكية المحفوظة بالمكتبة الأزهرية: مخطوط مختصر ترتيب المدارك وتقريب المسالك لمعرفة أعلام مذهب مالك للقاضي عياض لمؤلفه أبو عبد الله بن حمادة السبتي -الطبقة الثانية عشر- (Revue El-Wahat pour les Recherches et les Etudes, 2020)
Ceuta Is One Of The Most Important Cities That Played An Important Role In Enriching The Scientific And Cultural Life In Morocco. It Also Gave Birth To Scientists Who Have Been Credited With The Dissemination Of Various Sciences And Knowledge. Among The Famous Scientists In Ceuta Is Alqaddiayyadh. There Have Been Different Biographies Written About Alq’addiAyyadh To Introduce Him And Show The Great Impacts Of His Works. Among His Famous Works: Book Of The Order Of Perception And Approximation Of The Tract To Know The Flags Of The Doctrine Of Malik (Kitabtartibaltasawurwataqribalmasaliklimaerifat 'Aelameaqidatalmalik)   In Eight Parts. This Paper Addresses The Knowledge Of One Of Alq’ddihAyyadh’s Students Who Is The Moroccan Author Abu Abdullah Bin Hamada And Who Has Produced A Summary Of The Above Mentioned Book And Called It Brief Arrangement Of Perception. “Mukhtasartartibal’madarik” Manuscript.. Key Words- Alq’adsiAyyadh, Bin Homada, Mukhtasartartibal’madarik, “Malikii’s Flags “ “A’alamalmalikia”.